Sulfuric acid on breaking dormancy seeds, emergence and post-seminal morphology of Canna edulis L. - Pêgo, Rogério Gomes; Silva, Daniela Sousa da; Martins Filho, Sebastião; Grossi, Jose Antonio Saraiva (Ornamental Horticulture, 2016)
he objective of this study was to evaluate the efficiency of time scarification of seeds in sulfuric acid to break the dormancy of seeds, seedling emergence and post-seminal morphology of C. edulis. This way, were determined biometric characteristics of seeds with the help of pachymeter and digital balance. To dormancy breaking, the seeds were immersed in sulfuric acid during 0.0, 0.5, 1.0, 1.5, 2.0 and 2.5 hours and sown in sand in a condition greenhouse. After 21 days emergence percentage, emergence speed index (IVE), shoot length and seedling dry weight of plants were recorded. At 0, 2, 4, 8, 12, 16, 20 days after sowing, the seedlings taken digital images and post-seminal morphology was characterized. The fruit of C. edulis contains an average of 19.27 globoses seeds of black coloration measuring about 5.62 mm in diameter, the average weight of 1000 seeds is 128.8 grams. The highest percentage of seedling emergence of 60% and 90% are obtained from seed treated with 0.5 hours in sulfuric acid at 10 and 21 days after sowing, respectively. The seeds have hypogeal germination with development of fasciculate roots with root axes differentiated at 4 days after sowing. The protophyll is observed from the eighth day and the seedlings have intense purple coloration at 16 days after sowing.